3D GIS reconstruction of Hungarian Southern Defense Line - Juhász, Attila (Geodetski vestnik, 2024)
Remote sensing technologies and GIS have become every-day practice in military historical reconstruction. Our research employed laser scanning survey in conjunction with historical data to execute a detailed reconstruction of a common part of the Hungarian Southern Defence System. The system’s remaining objects are well documented and in good condition. However, the previous maps only provide approximate positions and fire directions. Currently, the objects are covered by extremely dense vegetation, making surveying particularly difficult. To overcome these challenges, both airborne and terrestrial laser scanning data collected and integrated. The 3D reconstruction of the defensive line had two major objectives. Firstly, to compare the reconstructed objects and their original plans based on 3D CAD models derived from in-field data. Secondly, to improve the historical military tactical maps, including object positions and orientations by the integration of 3D models into the digital terrain model from airborne scanning data. Finaly, the dimensions and the condition of the objects were analysed, and the defensive structure appearing on historical tactical maps was improved based on the surveyed data. The described methodology has the potential to reconstruct the entire fortified line, which could have archaeological, educational, architectural and tourism applications.
Keywords: 3D analysis; 3D object reconstruction; 3D rekonstrukcija objektov; daljinsko zaznavanje; lasersko skeniranje; LiDAR data integration; Madžarska; military; vojaška zgodovina